The enhancement of knowledge, preservation and valorisation of historical settlements in the alpine area: an interdisciplinary approach - Luisa Pedrazzini; Giulia Pesaro (European Regional Science Association (ERSA), 2004)
The paper aims to present the methodological approach used for the development of the Interreg IIIB Alpine Space project “Cultur ALP - Knowledge and Enhancement of Historical Centres and Cultural Landscape”. The project promoted by Lombardy Region, involves seven European regions from four different countries. The goal is to improve the knowledge of alpine historical settlements and to develop innovative operating policies to protect and enhance this distinctive cultural heritage. The paper will focus on the SWOT analysis methodology, here applied to cultural heritage and aiming to describe, understand and valorise the peculiarities and the values of historical settlements and cultural landscapes in the alpine territory. SWOT analysis indicators have been selected in order to internalise the interdisciplinary approach chosen in the project. The intervention strategy that normally characterises the government and management of historic settlements is sectoral and looks at the settlement itself as an ensemble of valuable buildings to be preserved from depletion. Here this point of view is overtaken in favour of a “systemic” analysis, where historical settlements can be viewed as cultural capital, closely integrated to all the other territorial resources. This to achieve a sustainable and durable territorial development, based on the preservation and valorisation of cultural, historical, artistic, social, economic and environmental identities, according to the peculiar spatial and socio-economic context of the Alps arch. This implies the contribution of different disciplinary approaches and tool boxes, that have to be understood and shared by different knowledge systems (approach, strategies, methodologies, tools…). The real challenge of the project is therefore the use of the interdisciplinary approach in developing integrated policies for the preservation and valorisation of historical settlements and cultural landscapes, pushing architects and historians of art as well as planners, economists, sociologists, administrative professionals and other territorial analysts to work together in a mutual learning process.
Keywords: 330